Indoor Navigation based on IndoorGML Case Study Rural and Surveying Engineering School, NTUA - TSANGOURI, AIKATERINI (Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2017)
Humans spend more of their daily life in indoor space, which becomes more complex due to urbanization and high density of population in a limited territory. In this manner, the navigation in indoor spaces becomes more and more required. Also, the recent progress of mobile devices and indoor positioning technologies could support location-based services in indoor space as well as outdoor space. However, there are many and significant differences between indoor and outdoor spaces and the geospatial technologies that have been developed for outdoors could not be applied for indoors. Indoor Navigation is a relatively new science that is under research. The Open Geospatial Consortium (OGC) in 2014 published a new standard called IndoorGML, which provide a standard data model and XML schema to represent and exchange indoor information, based on cellular space model. The main aim of IndoorGML is to provide interoperability between services and a data model framework for future development from simple indoor navigation services to complicated indoor spatial analysis and big data analysis. There are two methods to develop IndoorGML model, either from scratch by using an IndoorGML editor or by transforming existing indoor data from CityGML or IFC format in IndoorGML. The case study of this research, concerns the development of the IndoorGML model of the building complex of Rural and Surveying Engineering School of National Technical University of Athens. The model was developed by an Open Java IndoorGML editor (JInedit) and the model’s visualization was accomplished in a WebGL Viewer. IndoorGML models could be applied for emergency situations and also in connection with Land Administration Domain Model (LADM) in order to define the rooms’ use and the space accessibility depending on person’s status of rights.